Hans Driesch’s Interest in the Psychical Research. A Historical Study - Pareti, Germana (Medicina Historica, 2018)
In recent times the source of interest in psychical research in Germany has been subject of relevant studies. Not infrequently these works have dealt with this phenomenon through the interpretation of the various steps and transformations present in Hans Driesch’s thought, from biology and medicine to neovitalism, and finally to parapsychology. However these studies identified the causes of this growing involvement in paranormal research either in the historical context of “crisis” of modernity (or “crisis” in psychology), or in an attempt to “normalize” the supernatural as an alternative to the traditional experimental psychology. My paper aims instead at throwing light on the constant effort by Driesch to conceive (and found) psychical research as a science of the super-normal, using the methodology successfully adopted by the scientific community (especially German) in the late nineteenth century.